Improving the literation of city historical building with creative relieving coloring method (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
One important resource at the level of basic education is Human Resources which requires increased self-competence complementing life skills interrupted by the main tasks as teaching educators. SDIT Zahira, Medan in its educational activities refers to increasing socio-cultural literacy. So far the curriculum has not taught specifically about the social capital of pride in the city of Medan as a specific local content curriculum development. With the learning method through coloring creative relieving coloring book which is very meaningful for children's emotional control, it is used in accelerating literacy learning about the local wisdom of the historic architecture of Medan city. For this, the Universitas Sumatera Utara Community Service Team TALENTA 2019 conducted activities with teachers starting with an introduction and understanding of the rich architecture of the historic city of Medan in the form of scientific exposure and continued with training in the procurement of teaching materials for creative relieving coloring books, testing the use of materials teaching and creativity training on the use of textbooks in the realm of entrepreneurship.